Avaliando a política de educação ambiental nas escolas do Mato Grosso: desafios entre os domínios da governança e da governabilidade - Pedrotti-Mansilla, Débora Eriléia (2010)
To overcome the scenarios of environmental degradation in the State of Mato Grosso, requires a dialogical model between schools, communities and government to order the construction and implementation of Public Policies for Environmental Education. This thesis aimed to understand the policy in environmental education of the State Department of Education, as an unfinished process, with the possibility of reversing unwanted scenarios for social control exercise their power of coauthorship and citizenship. In order to meet this goal, we used throughout the thesis based on qualitative research methodologies, participatory research, bibliographic and documental research diagnostic evaluation, in search of hybridization between the evaluation results and processes, observing the natural phenomenon. The sustainability analysis was infused, initially for a critical educational praxis of Environmental Education in the Learning System TM. And in understanding the process used to formulate public policies in Mato Grosso, in the ethical axiom of non-neutrality of subjects, establishing dialogues with SEDUC MT, Researcher Group on Environmental Education and Training Centres of Vocational Education Basic. By launching an evaluative look on Policy Environmental Education, focusing on the educational materials, the tactics of implementation. The results are offered prognoses of the construction and implementation of the Environmental Education Policy SEDUC MT (PREA). The path ahead for construction of Public Policies for Environmental Education in the spaces must be limited by the educated social participation, since its construction process (initial proposal) to its evaluation. "Learning with the error" this is the tactic that could revive the school units of Mato Grosso Environmental Education, but greatly participatory, with the audience needed to bring schools and communities feel part of their formative processes and decision-making, it based the political processes necessary for teaching an education policy that is environmentally and in search of a more just and sustainable..